Luminescent and magnetic properties of Fe3O4@SiO2:phen:Eu3+ - Silva, Raphael Lucas de Sousa (2017)
Magnetite was doped with rare earth ions (europium) to produce core-shell materials with both magnetic and luminescent properties, i.e., a magnetic Fe3O4 oxide core and a SiO2:phen:Eu3+ shell. The resulting material was analyzed by X-ray powder diffraction and transmission electron microscopy, and subjected to magnetic and luminescence emission measurements. All the synthesized materials exhibited superparamagnetic behavior and luminescence emission. The magnetic behavior of Fe3O4 and luminescence emission of SiO2:phen:Eu3+ of the materials were compared to precursors.